Influencia del hábitats en la producción de alcaloides de la raíz de Tabernaemontana heterophylla, Vahl (lobo sanango) en dos localidades de la provincia de Maynas-2019 - Ríos Ríos, Jorge Manasés (2023)
Chemical compounds, including isolated alkaloids from plant species, are widely used in the pharmaceutical industry. The objective of the thesis was to determine to what extent habitats influence the production of alkaloids in the root of Tabernaemontana heterophylla (Vahl) in two locations in the Province of Maynas. Floristic analysis was carried out according to the Mueller-Dombois methodology, soil analysis was performed using the laboratory method suggested by Champan, ethanolic extracts were prepared, different chromatographic techniques were used to obtain pure alkaloids, and chemical estructures were identified using spectroscopic and spectrometric methods. The results show the predominant presence of the plant family Moraceae at 18.44% in Manacamiri and Piperaceae at 18.67% in Mazan. The soils are very similar in both study areas, with highly acidic pH, low organic matter, and a texture ranging from loamy clay to sandy. Potassium, phosphorus, and cation exchange capacity are low to medium in both areas. In the Manacamiri area, the following pure compounds were identified: Heyneanina, Olivacine, and Voacamine. In the Mazan area, Voacangina Hydroxyindolenina, Voacangina, Olivacina were identified. It is concluded that the chemical composition in terms of alkaloid content, there is variability with the exception of Olivacine and in relation to the habitat (floristics and soil), there is no variability